A review on non-polyphenolic and terpenoid phytoconstituents with antioxidant and cytotoxic potential - Ahmed, Kazi Zeba (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2021.